Information Technology Adoption and Knowledge Sharing Intention: The Mediating Role of Leadership Style - Widodo, Adi; Putra, Firdaus; Nadeak, Multi; Novitasari, Dewiana; Asbari, Masduki (IJOSMAS, 2022)
The purpose of this study is to investigate the effect of information technology adoption on knowledge sharing intention by involving the leadership style variable as a mediator. The sample of this research was taken from 102 lecturers of a private university in Indonesia using a simple random sampling technique and using SEM (Structural Equation Model) with SmartPLS version 3.0 software as a statistical tool. The results of this study indicate that information technology adoption has a positive and significant effect on knowledge sharing intention, either directly or through leadership style mediation. Therefore, leadership style can be a variable mediator that strengthens the influence of information technology adoption on knowledge sharing intention.